Analysis of TPMDK Abilities of Prospective Mathematics Teachers Based on Semester Level and Gender - Toheri Toheri; Yandi Heryandi (Journal of General Education and Humanities, 2026)
This research aims to (1) describe the level of mastery of TPMK of prospective mathematics teachers; (2) examine the aspects of TPMK that prospective mathematics teachers dominate. (3) Analyze the differences in the ability of TPMK of prospective mathematics teachers based on semester and gender. This research uses a quantitative approach, with a survey method. The survey was conducted to collect data from respondents regarding the TPMDK (Technological-Pedagogical Mathematics Dimension Knowledge). The population is all prospective math teachers in Region III, Cirebon. The sample was a proportional random sample of prospective math teachers. The results showed that (1) TPMDK ability obtained an average of 2.983, which is included in the high category. Students of prospective mathematics teachers in Region III Cirebon have the knowledge and skills needed by mathematics teachers to integrate technology effectively into pedagogy and high mathematics content. (2) The ability of TPMDK when viewed from the knowledge dimension, in order from the highest is the Factual Dimension (3.09), Metacognitive dimension (3.00), Conceptual dimension (2.96), and procedural dimension (2.94). The tendency toward mastery of technological knowledge and its relation to other knowledge drives high ability in other areas. This is evident in the ability of Technological Factual Knowledge and Technological Conceptual Knowledge.